Exercise-Induced Ventricular Fibrillation: Seven Years Follow-Up - (:unkn) unknown (AVES YAYINCILIK, 2011)
We present a 7-year follow-up of a 55-year-old male who experienced ventricular fibrillation during the recovery period of exercise testing and refused implantation of an ICD. Normal left ventricular systolic function was found on echocardiographic examination, and coronary angiography revealed only a side branch disease with a vessel diameter of less than 2 millimeters. The patient was discharged on metoprolol and ASA in addition to his previous treatment with lisinopril and simvastatin. Outpatient cardiac evaluation by repeated 24-hour ECG monitorizations (Holter) revealed normal findings. On follow up visits every six months for the past seven years, the patient was found to be asymptomatic.
Keywords: Ventricular fibrillation; exercise test; TACHYCARDIA